Improving Preventive Care for Children With Sickle Cell Anemia: A Quality Improvement Initiative. Issue 1 (28th January 2021) - Cabana, Michael D.; Marsh, Anne; Treadwell, Marsha J.; Stemmler, Peggy; Rowland, Michael; Bender, M. A.; Bhasin, Neha; Chung, Jong H.; Hassell, Kathryn; Abdul Rashid, N. F. Nik; Wong, Trisha E.; Bardach, Naomi S.
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Sickle cell disease is a complex chronic disorder associated with increased morbidity and early mortality. The Pediatric Quality Measures Program has developed new sickle cell-specific quality measures focused on hydroxyurea (HU) counseling and annual transcranial Doppler (TCD) screening; however, these measures have not been used in a clinical setting to inform quality improvement (QI) efforts. Methods: From 2017 to 2018, 9 sickle cell subspecialty clinics from the Pacific Sickle Cell Regional Collaborative conducted a year-long QI collaborative focused on improving the percentage of patients with HU counseling and TCD screening based on the new quality measures. After an initial kick-off meeting, the 9 sites participated in monthly conference calls. We used run charts annotated with plan-do-study-act cycle activities to track each site's monthly progress and the overall mean percentage for the entire collaborative. Results: There was an overall improvement in the aggregate HU counseling from 85% to 98% ( P < 0.01). For TCD screening, referral frequency changed from 85% to 90% ( P = 0.76). For both measures, the variation in frequencies decreased over the year. Conclusion: Over 1 year, we found that a regional QI collaborative increased HU counseling. Although referral for TCD screening increased, there was no overall change in TCD completion. Overall, this QI report's findings can help clinicians adopt and implement these quality measures to improve outcomes in children.